Genetic predisposition to elevated BMI and adult asthma phenotypes in a Japanese population - Yohei Yatagai; Hisayuki Oshima; Yu Abe; Haruna Kitazawa; Hironori Masuko; Takashi Naito; Takefumi Saito; Tomomitsu Hirota; Mayumi Tamari; Emiko Noguchi; Tohru Sakamoto; Nobuyuki Hizawa (PLoS ONE, 2026)
Obesity is a well-established risk factor for asthma, with genetic factors influencing both conditions. This study investigates the impact of genetic predisposition to increased body mass index (BMI) on adult asthma phenotypes. We recruited 1532 non-asthmatic healthy individuals and 779 adult asthma patients to assess the relationship between BMI-related genetic risk scores (BMI-GRS) and asthma. Among the 85 single nucleotide polymorphisms (SNPs) previously associated with BMI in Japanese populations, significant associations with BMI were confirmed for 6 SNPs in the healthy individuals. Using these, BMI-GRS was calculated for both groups. While asthma patients had higher BMI than healthy individuals (p = 0.004), no significant difference in BMI-GRS was observed between the groups (p = 0.56). A cluster analysis identified six distinct phenotypes of adult asthma patients: two overweight/obese clusters (one with elevated BMI-GRS, one without) and four non-obese clusters (with one showing significantly elevated BMI-GRS). This study demonstrates a genetic heterogeneity in the phenotype of adult asthma among a Japanese population, showing that genetic variants associated with BMI contribute to specific subtypes of asthma. Prospective longitudinal studies are essential to delineate the interactions between genetic predisposition, elevated BMI, subsequent changes in adiposity, and the evolution of asthma phenotypes, which would facilitate the development of mechanism-based therapeutic strategies tailored to genetically-defined patient subgroups.